2022
DOI: 10.1093/ajcn/nqac219
|View full text |Cite
|
Sign up to set email alerts
|

Long-term diet and risk of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection and Coronavirus Disease 2019 (COVID-19) severity

Abstract: Background The role of diet on COVID-19 is emerging. Methods We included 42,935 participants aged 55 to 99 years in two ongoing cohort studies, Nurses’ Health Study II and Health Professionals Follow-up Study, who completed a series of COVID-19 surveys in 2020 and 2021. Using data from food frequency questionnaires prior to COVID-19, we assessed diet quality using the Alternative Healthy Eating Index (AHEI)-2010, the alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 43 publications
0
28
0
1
Order By: Relevance
“…Five studies involving 4 907 637 individuals (3 149 784 high‐quality diet individuals and 1 757 853 controls) reported the risk of COVID‐19 infection in individuals with high‐quality dietary pattern 4–8,18 . Overall pooled analyses showed a 28% decrease of COVID‐19 infection was associated with high‐quality dietary patterns (RR = 0.72, 95% CI 0.64–0.81, p = 0.00001; Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies involving 4 907 637 individuals (3 149 784 high‐quality diet individuals and 1 757 853 controls) reported the risk of COVID‐19 infection in individuals with high‐quality dietary pattern 4–8,18 . Overall pooled analyses showed a 28% decrease of COVID‐19 infection was associated with high‐quality dietary patterns (RR = 0.72, 95% CI 0.64–0.81, p = 0.00001; Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…We identified five studies involving 4 023 663 individuals (3 149 784 high‐quality diet individuals and 873 881 controls) addressing the effects of different high‐quality dietary patterns on COVID‐19 infection and hospitalization (Figure 1 ). Reports were published between 2021 and 2022 using the following experimental designs: three cohorts 6 , 7 , 8 and two cross‐sectional studies. 4 , 5 Except for two cross‐sectional studies, all cohorts reported the prevalence of comorbidity, including hypertension, diabetes mellitus, cardiovascular disease, and pulmonary disease among included individuals.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations